-40-8x=-5(5+3x)+2x

Simple and best practice solution for -40-8x=-5(5+3x)+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -40-8x=-5(5+3x)+2x equation:


-40-8x=-5(5+3x)+2x

We simplify the equation to the form, which is simple to understand
-40-8x=-5(5+3x)+2x

Reorder the terms in parentheses
-40-8x=+(-25-15x)+2x

Remove unnecessary parentheses
-40-8x=-25-15x+2x

We move all terms containing x to the left and all other terms to the right.
-8x+15x-2x=-25+40

We simplify left and right side of the equation.
+5x=+15

We divide both sides of the equation by 5 to get x.
x=3

See similar equations:

| 12x+9-4x-3= | | 3.3(x-2)=-13.2 | | 2x^2-4x+200= | | 5x^2-12+4=0 | | -6x-7y=-11 | | -5-4(-4+7x)=-6x-33 | | 6x-3-9x+9= | | 5*25= | | I-5.13=2.9 | | 9v=0 | | f(x)=sin(x)ln(5x) | | 27x-24y=12 | | x^2+39x-8=0 | | 5x^2+40x=25 | | -5(6x-5)=8x+25 | | -8(-5-4x)=-36-6x | | 4X+16=28-2X | | -(3-2x)=-x+21 | | 4x-3-x^2=0 | | -8(-3x+5)-7(-4x+(-9))=0 | | 4n+12.4=-6.8 | | -(3b+4)=-4b | | f(x)=0.9(0.6) | | y^2-16y-10=26 | | cos*2x-5*cosx+3=0 | | 6x^2-17x+1=0 | | 7x-2y+5=0 | | 4n-12.4=-6.8 | | y^2=2y+35 | | sin(12x)-sin(6x)=0 | | 9w-8w+4=0 | | -32x--48=-33-5x |

Equations solver categories